Strategi Humas TVRI Dalam Memperbaiki Citra TVRI Di Mata Publik - Wina Puspita Sari; Indah Nursyamsiah (Communicology: Jurnal Ilmu Komunikasi, 2013)
Abstract TVRI is the oldest public station tv in Indonesia. Nowadays, TVRI has many competitors such as several national station tv and cable tv. Slowly but sure, TVRI left by it audiences. The current image of TVRI is out of date and the program is un interesting to see so that public relations officers of TVRI have to do some strategy to fix their image in order to have their audience back. Keyword :Public Relations Strategy, Image